Relationship between nutritional status and the systemic inflammatory response: micronutrients - McMillan, Donald C.; Maguire, Donogh; Talwar, Dinesh (Proceedings of the Nutrition Society, 2019)
Micronutrients such as trace elements and vitamins are important as enzyme cofactors in the metabolism of all cells in the body and therefore key to determining nutritional status. The present systematic review examined the evidence of the impact of the systemic inflammatory response on plasma micronutrient status in acute (surgical) and chronic tissue injury. A literature review using targeted subject headings was carried out. Plasma C-reactive protein was used to classify minor (<10 mg/l), moderate (11–80 mg/l) and major (>80 mg/l) inflammation. The literature search produced 2344 publications and plasma vitamin D, zinc and carotenoids were most commonly studied and plasma vitamins K, B2 and B6 were least studied. In acute injury thirteen studies (all prospective) and in chronic injury twenty-four studies (largely retrospective) were included in the review. There was consistent evidence that most common measured micronutrients in the plasma (zinc, selenium, vitamins A, D, E, K, B2, B6, B12, C, lutein, lycopene, α- and β-carotene) were significantly lowered from minor to moderate to major inflammation. The results of the present systematic review indicate that most plasma micronutrients fall as part of the systemic inflammatory response irrespective of acute or chronic injury. Therefore, in the presence of a systemic inflammation, plasma micronutrient concentrations should be interpreted with caution. There are a number of methods applied to adjust plasma micronutrient concentrations to avoid misdiagnosis of deficiency. Alternatively, intracellular measurements appear to obviate the need for such plasma adjustment to assess micronutrient status.